Effects of social organisation on feeding behaviour in growing pigs - Bornett, Hannah Louise Imogen (The University of Edinburgh, 2001)
Group housed pigs make less frequent feeder visits of a longer duration, and eat at faster rate than pigs housed individually. They also have lower growth rates which may be due to elevated stress associated with aggression and social stress. The aim of this thesis is to investigate the stability o f feeding patterns in individual pigs, the effect of grouping and group composition on feeding patterns and to assess the consequences of this shift in feeding behaviour for the welfare and performance of grouped pigs. The flexibility of feeding behaviour was assessed by restricting the time of access to food of previously ad libitum fed pigs to 2 hours per day and then returning them to 24 hr access. When pigs had restricted access to food they made fewer daily feeder visits, of a longer duration, with a higher food intake per visit than the control pigs that had 24 hour access to food throughout. Flexibility was assessed by comparing feeding behaviour before and after restriction. The pigs that experienced a period of restricted feeding either resumed their previous behaviour or showed the same trend as the controls. It was concluded that feeding behaviour was flexible. A second experiment investigated the effect of grouping on feeding behaviour. Pigs were housed individually for 3 weeks after which they were combined into groups o f 4 for 3 weeks, before being returned to individual housing for a further 3 weeks. When grouped, pigs made fewer visits to the feeder of a longer duration than when they were housed individually. Possible explanations for the changes in feeding behaviour are competition, group cohesion, or that the high frequency of feeder visits when the pigs are housed individually is a consequence of a lack of social stimulation. The results suggest that group cohesion is most likely to have been causal in the observed changes in feeding behaviour. A final experiment investigated the effect of group composition in terms of latent aggressiveness on feeding behaviour. Pigs were kept in litter-groups for 3 weeks from weaning and categorised as ‘High’ (H) or ‘Low ’ (L) aggressive using an attack latency test. They were then transferred to individual housing for 2 weeks and their feeding behaviour was recorded. In a final 3 week period the pigs were combined into groups o f 8 pigs o f either all H or all L aggressiveness. Pigs in H groups had higher aggression levels on the day of mixing than pigs in L groups and salivary cortisol concentrations suggest that stress levels may have been elevated when the pigs were grouped. Feeding behaviour changed between individual and group housing in accordance with Experiment 2. There were no differences in feeding behaviour, defined in terms o f visits, between pigs in H groups and pigs in L groups. However, when visits were organised into meals it was found that H pigs had more meals per day with longer within meal intervals both when individually and group housed. This suggests that there may be a link between aggressiveness o f individuals and meal patterns. In conclusion, pigs have flexible feeding patterns in terms of a change in time of access to food. Pigs alter their feeding behaviour when group housed in the direction o f fewer feeder visits o f a longer duration, probably due to the effects o f group cohesion. The aggressiveness o f individuals within a group had no effect on feeding behaviour. There is potential to categorise the aggressiveness o f pigs using feeding behaviour such that aggressiveness could be manipulated in breeding programmes.
The effects of social organisation on feeding behaviour in growing pigs